Prevalence and genotype distribution of human papillomavirus among women with cervical lesions in Shenzhen city, China - Qingfeng Mai; Xiaohan Yang; Huan Cheng; Genghang Wu; Zikun Wu (Taylor & Francis Group, 2021)
There is currently a lack of sufficient data on human papillomavirus (HPV)-attributable cervical carcinoma in China. Accordingly, we aimed to determine the prevalence and genotype distribution of HPV among women with cervical lesions in Shenzhen, in order to evaluate the potential benefit of HPV vaccination programs and inform cervical cancer control policies. We enrolled 5,255 patients who were admitted to the University of Chinese Academy of Sciences Shenzhen Hospital from January 2017 to December 2019. The HPV prevalence and genotype distribution were analyzed using the 21 HPV GenoArray diagnostic assay. A total of 937/5,255 patients showed HPV-positivity (prevalence rate 17.83%), of whom 85.81% (804/937) had high-risk HPV infection. HPV52 was the most prevalent genotype (4.72%, 248/5,255), followed by HPV58 (3.04%, 160/5,255), and HPV16 (2.72%, 143/5,255). The HPV prevalence rates among women with a normal cervix, low-grade intraepithelial lesions, high-grade intraepithelial lesions, invasive cervical cancer, and other characteristics were 15.63% (50/320), 58.65% (61/104), 80.00% (44/55), 88.57% (31/35), and 15.84% (751/4,741), respectively. HPV16, HPV18, and HPV52 accounted for the majority of cervical lesions, and the infection rates of HPV16 and HPV18 gradually increased with intraepithelial lesion progression (both P < .001). Our study found that HPV16, HPV52, and HPV18 played important roles in the occurrence and development of cervical lesions. This finding has the potential to guide the formulation of HPV screening and vaccination programs and preventive strategies for HPV-attributable cancer in this region.